Introduction to clinical in vivo MR spectroscopy - Hajek, Milan; Dezortova, Monika (European journal of radiology, 2008)
A short introduction to the description of in vivo (1)H MR spectra is given. The parameters important for successful measurement and interpretation of spectra are discussed. Basic metabolites visible in proton MR spectra are described and the attention is paid to N acetylaspartate, creatine and cholines.
Keywords: Aspartic Acid; Choline; kyselina asparagová; Brain Chemistry; Humans; lidé; cholin; mozek - chemie; Magnetic Resonance Spectroscopy; mozek; kreatin; Brain; magnetická rezonanční spektroskopie; Creatine